Effect of thermal conditioning during embryonic development on aspects of physiological responses of broilers to heat stress - Moraes, VMB; Malheiros, R. D.; Bruggeman, V; Collin, A.; Tona, K.; Van As, P.; Onagbesan, O. M.; Buyse, J.; Decuypere, E.; Macari, Marcos [UNESP] (Elsevier B.V., 2003)
The purpose of the present study was to investigate the effect of thermal conditioning, (through exposure to heat stress), during pre-hatch development on some physiological responses of post-hatch broilers to a post-natal heat stress challenge. Exposure to heat stress at this stage, we hope, may possibly induce epigenetic heat adaptation. Incubating eggs were exposed to temperature of 39.0degreesC for 2 h from Day 13 to 17 of incubation. At 33, 35, 37, 39, 41 and 43 d of age, the broilers hatched from these eggs were housed individually in open-circuit respiration cells. The climatic chambers were set to 22degreesC and increased to 30degreesC for 4 h. O-2 consumption and CO2 production of each chicken was monitored continuously in order to calculate the heat production. Blood samples were obtained before and during the 4 h heat stress. Thermal conditioning during incubation did not affect the plasma T-4, corticosterone, glucose, uric acid and CK concentrations. Temperature challenge, decreased plasma T-3 of broilers of both groups but the decrease was greater in pre-conditioned broilers compared with controls. A similar trend was observed for triglycerides. These changes did not affect total heat production. Since decreased T3 and triglyceride levels are part of the mechanisms for thermoregulation, these suggest that thermal conditioning during incubation can improve the broiler chicken capability for thermotolerance at later post-hatch age. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: thermal conditioning; heat stress; incubation; thyroid hormones; heat production; corticosterone